Sabriel - Nix, Garth (New York : HarperTrophy, 1997)
Sabriel, daughter of the necromancer Abhorsen, must journey into the mysterious and magical Old Kingdom to rescue her father from the Land of the Dead.
"First published in 1995 by HarperCollins"--T.p. verso.
1060
Accelerated Reader AR
"An ALA Notable Book"--P. [4] of cover.
"Winner of the Aurealis Award for Excellence in Australian science fiction"--P. [4] of cover.
Keywords: Magic -- Juvenile fiction; Magical thinking -- Juvenile fiction; Fantasy fiction; Love stories; Romantic suspense fiction